DISCRIMINATION OF PUBLIC SERVICE IN POPULATION AND CIVIL REGISTRATION AGENCY NORTH LAMPUNG REGENCY - Rahadian Aksa (Yogyakarta State University, 2018)
The objective of this research is to determine the forms and causes of discrimination in the services delivery provision of North Lampung population and civil registration agency. The research was a descriptive qualitative. Research results showed the prevalence of discriminatory practices in the delivery of services in the Population and Civil Registration agency in North Lampung Regency. Dissemination took forms of time required, and cost incurred to obtain services, attitude of service providers, and procedures that differed between those that applied to ordinary citizens (long and tedious) and for others (short and quick) that included the rich, officials, community leaders and relatives or acquaintances of population and civil registration agency. However, there was no evidence of discrimination in service delivery that was based on race and religion. Culture, as manifested in paternalistic form and bureaucratic hierarchy was the main cause of discrimination in the services delivery in population and civil registration agency. Thus, paternalism and bureaucracy culture underlie favoritism accorded to officials and rulers, individuals in key positions of government and society, and relatives and acquaintances of employees in the agency as opposed to other members of society.